Business Law - Andrew Gibson; Douglas Fraser (China Pearson, 2005)
Provides students of business or commercial law with an accessible but authoritative and comprehensive textbook. Offers a thorough coverage of business law topics and considers the legal environment in which business must operate.
Keywords: Business law; Commercial law